Synthesis and Characterization of Nanocomposites Tin Oxide-Graphene Doping Pd Using Polyol Method - Aminuddin Debataraja; Robeth Viktoria Manurung; Lia A.T.W. Asri; Brian Yuliarto; Nugraha Nugraha; Bambang Sunendar (Universitas Gadjah Mada, 2018)
This paper report on polyol method for Pd doped tin oxide-graphene nanocomposite thin film. XRD result shows sharp peaks at certain 2θ value and match with tin oxide, graphene, and Pd database. FTIR result shows peak from alcohol chain for –OH strong bonded absorption (3444 cm-1), also there are aldehyde and ketone which are indicated by C=O strong absorption (1751 cm-1). Moreover, alkene is also formed for decreasing symmetry intensity C=C (1616 cm-1), while alkyne is formed at strong deformation absorption at 646 and 613 cm-1. SEM and TEM result show SnO2 particles are attached uniformly on graphene surface layer. The composition for C, O, Sn, and Pd are 33.13, 25.58, 35.35 and 5.94%, respectively. This result indicated that the good composition is formed for Pd doped SnO2-graphene nanocomposite. The nanocomposite is promising materials for toxic gas sensor application at low temperature.